PELATIHAN PENINGAKTAN KAPASITAS PEMUDA UNTUK BELA NEGARA DALAM MENYONGSONG HARI PROKLAMASI KEMERDEKAAN RI 17 AGUSTUS 1945 DI TAHUN 2025 - Daholu, Ahmad; Suriadi, Suriadi; Azaluddin, Azaluddin; Tri Pratiwi, Endang; Jasiyah, Rabiyatul; Malik, Ernawati (Jurnal Pengabdian Masyarakat Sabangka, 2025)
This community service (PKM) activity was implemented in the form of training to increase the capacity of youth to defend the nation in Lapandewa Kaindewa Village, Lapandea District, South Buton Regency. The background to this activity was the challenge of declining nationalism and the weakening understanding of national values among the younger generation amidst the rapid flow of globalization. The method used was a qualitative descriptive approa ch, involving 40 participants consisting of village youth, youth organizations, and local youth leaders. The activity was carried out through the delivery of national insight and discipline, and included a follow-up plan. The results of this activity showed a significant increase in the training participants' understanding of the concept of national defense. The impact of this activity was felt not only by the participants but also by the wider community, with community enthusiasm and commitment to establishing a youth forum for nation al defense as a follow-up. Thus, this PKM makes a tangible contributi on to developing youth with a patriotic character and a role in nation al development in general and regional development in particular